1993
DOI: 10.1002/eji.1830230724
|View full text |Cite
|
Sign up to set email alerts
|

Propriocidal apoptosis of mature T lymphocytes occurs at S phase of the cell cycle

Abstract: We found that mature nontransformed CD4+ and CD8+ T lymphocytes could be made susceptible to T cell receptor(TcR)-mediated apoptosis by pretreatment with interleukin-4 (IL-4) or interleukin-2 (IL-2). The degree of susceptibility to death could be correlated with the level of cell cycling as measured by thymidine incorporation, cell doubling times, or the number of cells incorporating bromodeoxyuridine during S phase. However, using pharmacologic cell cycle blocking agents, we found that progression through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
6
4

Year Published

1997
1997
2005
2005

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 248 publications
(159 citation statements)
references
References 50 publications
5
144
6
4
Order By: Relevance
“…Preincubation of the cells with FCM, IFN-␣, or IFN-␤ for 1 h significantly increased the viable cell recovery after peptide activation at all concentrations tested ( p Ͻ 0.005 for FCM and p Ͻ 0.05 for IFN-␣␤, respectively). Preincubation of the cells with IL-2 did not rescue from peptide-induced death as previously described (23). IFN-␣␤ and FCM also blocked cell death and increased cell recovery of 7P.24 cells induced by the direct addition of an agonistic CD95-Ab rather than by peptide (Fig.…”
Section: Ifn-␤ Is the Main Anti-apoptotic Mediator In Fcmsupporting
confidence: 71%
“…Preincubation of the cells with FCM, IFN-␣, or IFN-␤ for 1 h significantly increased the viable cell recovery after peptide activation at all concentrations tested ( p Ͻ 0.005 for FCM and p Ͻ 0.05 for IFN-␣␤, respectively). Preincubation of the cells with IL-2 did not rescue from peptide-induced death as previously described (23). IFN-␣␤ and FCM also blocked cell death and increased cell recovery of 7P.24 cells induced by the direct addition of an agonistic CD95-Ab rather than by peptide (Fig.…”
Section: Ifn-␤ Is the Main Anti-apoptotic Mediator In Fcmsupporting
confidence: 71%
“…It has been reported that the B cell marker B220 is up-regulated on activated T cell blasts before entering apoptosis (27,35,36). Considering that nasal tissues are an overexposed environment, it can be hypothesized that cells from NALT undergo apoptosis after activation by exogenous Ags or superantigen, as previously demonstrated in other experimental systems (27,35,37,38). However, the expression levels of both CD45RB and activation markers suggests that the majority of cells from NALT corresponded to naive T cells (CD45RB high ).…”
Section: Discussionmentioning
confidence: 83%
“…After overnight culture, thymocytes were harvested, and cell death was measured as previously described (27)(28)(29). These previous studies have shown that this method accurately assesses cell loss resulting from T cell apoptosis.…”
Section: In Vitro Cell Death Assaymentioning
confidence: 99%